2012
DOI: 10.1103/physrevc.86.044328
|View full text |Cite
|
Sign up to set email alerts
|

Absolute partial decay-branch measurements in13C

Abstract: The 9 Be( 6 Li, d) 13 C * reaction at a beam energy of 42 MeV has been investigated using a large-acceptance silicon-strip detector array and the high-resolution Q3D magnetic spectrograph. The Q3D facilitated the unambiguous determination of the reaction channel via identification of the deuteron ejectile, thereby providing the spectrum of excited states in 13 C in the range from 10.7 to 15.0 MeV. The silicon array was used to detect and identify the 13 C recoil-breakup products with efficiencies of up to 49%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
(57 reference statements)
3
11
0
Order By: Relevance
“…In the present work, the band is extended up to J π = (8 − ). Wheldon et al [9] also reported levels at 710.2(15) keV and 953.3 (20) keV, but they were not placed in the K π = 4 − band, as proposed here. The previously known K π = (6 + ) state [8,14] is also confirmed in the present work, and the 217.6-keV γ ray is interpreted as the first in-band cascade transition.…”
Section: supporting
confidence: 43%
See 1 more Smart Citation
“…In the present work, the band is extended up to J π = (8 − ). Wheldon et al [9] also reported levels at 710.2(15) keV and 953.3 (20) keV, but they were not placed in the K π = 4 − band, as proposed here. The previously known K π = (6 + ) state [8,14] is also confirmed in the present work, and the 217.6-keV γ ray is interpreted as the first in-band cascade transition.…”
Section: supporting
confidence: 43%
“…[7]. Wheldon et al [9], using the (p,d) reaction and a highresolution magnetic spectrograph, observed a number of two-quasiparticle excited states in 186 Re. However, because of a lack of angular distribution data, the spin, parity, and configuration assignments were based on model calculations rather than on experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Among the carbon isotopes, 13 C is of particular importance as the system composed of three α particles (bosons) plus a valence nucleon (fermion). The Hoyle analog state in 13 C, the BEC of three α particles with a neutron as an impurity, and the possible formation of the linear-chain structure assisted by a valence neutron have been main interests for this nucleus [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the experimental C0 matrix elements, the IS monopole transition rates of 13 C for the lowest three excited 1/2 − states have been reported with the inelastic α scattering on the target of 13 C by Kawabata et al [37], and their experimental values are comparable to the single particle one [8]. In the light of the fact that the monopole strengths are one of the good physical quantities to explore cluster states in light nuclei as mentioned above, those experimental results suggest that the low-lying excited 1/2 − states have an aspect of α-clustering in 13 C. Candidates for the molecular states with K π = 3/2 ± [69][70][71] and linear-chain configurations of three α clusters in 13 C [69, [72][73][74] have been proposed in highly excited energy region above the 3α + n threshold. However, the cluster structures of the low-lying states including the 1/2 ± ones up to around the 3α + n threshold have not been studied well, although some preliminary results have been reported [38,69,75].…”
Section: Introductionmentioning
confidence: 78%